Predictors of metformin monotherapy failure in gestational diabetes mellitus. Issue 5 (10th May 2022) - Benido Silva, Vânia; Fonseca, Liliana; Pereira, Maria Teresa; Vilaverde, Joana; Pinto, Clara; Pichel, Fernando; Almeida, Maria do Céu; Dores, Jorge
Abstract : Objective: Metformin has emerged as a safe and effective pharmacological alternative to insulin in gestational diabetes mellitus (GDM), being associated with lower maternal weight gain and hypoglycemia risk. Nevertheless, glycemic control is unaccomplished in a considerable proportion of women only treated with metformin. We aim to determine the metformin monotherapy failure rate in GDM and to identify predictors of its occurrence. Design and methods: This was a retrospective multicenter study including pregnant women with GDM patients who started metformin as a first-line pharmacological treatment ( n = 2891). A comparative analysis of clinical and analytical data between the group of women treated with metformin monotherapy and those needing combined therapy with insulin was performed. Results: In 685 (23.7%) women with GDM, combined therapy to achieve adequate glycemic control was required. Higher pregestational BMI (OR 1.039; CI 95% 1.008–1.071; P -value = 0.013), higher fasting plasma glucose (PG) levels in oral glucose tolerance test (OGTT) (OR 1.047; CI 95% 1.028–1.066; P -value <0.001) and an earlier gestational age (GA) at metformin introduction (0.839; CI 95% 0.796–0.885, P -value < 0.001) were independent predictive factors for metformin monotherapy failure. The best predictive cutoff values were a fasting PG in OGTT ≥87 mg/dL and GA at metformin introduction ≤29 weeks. Conclusions: In 685 (23.7%) women, combined therapy with insulin to reach glycemic control was required. Higher pre-gestational BMI, fasting PG levels in OGTT ≥87 mg/dL and introduction of metformin ≤29 weeks of GA were independent predictive factors for metformin monotherapy failure. The early recognition of these characteristics can contribute to the establishment of individualized therapeutic strategies and attain better metabolic control during pregnancy.